Language Variation: Code-Mixing Done by Yahukimo Students - Dewi, Pradnya Paramita; Suyarmanto, Suyarmanto; Dapla, Melky (Universitas Islam Negeri Raden Intan Lampung, 2023)
Multilingual individuals, who possess proficiency in multiple languages and an understanding of their structures, often engage in code-mixing as a means of communication. This study aims to explore the code-mixing patterns exhibited by Yahukimo students residing in Malang, as well as the underlying motivations for their code-mixing practices. Employing a descriptive qualitative research design, the study identifies two predominant types of code-mixing: insertion and congruent lexicalization, which are influenced by the linguistic structures of the languages involved. Additionally, the variation in code-mixing is classified into inner and outer code-mixing. The findings indicate that Yahukimo students employ code-mixing as a means of fostering solidarity and navigating social and cultural distances. This research provides valuable insights into the intricate dynamics of language use and contributes to our understanding of the phenomenon of code-mixing